Analisis Prediksi Jumlah Pengunjung Perpustakaan Berdasarkan Jenis Kelamin di Kabupaten Malang dengan Menggunakan Metode Monte Carlo - Rifki, Achmad; Muhammad Fikrul Azizi; Soffiana Agustin (Jurnal Teknik Informatika dan Komputer, 2024)
Libraries are crucial institutions supporting the development of education and knowledge within society. As centers of information, they serve not only as repositories for books and other informational resources but also as spaces for learning and interaction for diverse segments of the population. Therefore, understanding visitor numbers and their visiting patterns is crucial for library managers to enhance planning and optimize services. This study aims to analyze predictions of library visitor numbers in Malang Regency using the Monte Carlo method. The research utilizes data on visitor counts by gender from 2018 to 2020 obtained from the Department of Libraries and Archives in Malang Regency. These data will be used to forecast visitor numbers for the years 2019 to 2021. The analysis reveals that the most accurate prediction occurred in 2019, achieving a 52% accuracy rate. Lower accuracy in subsequent years was attributed to the COVID-19 pandemic, which restricted public movement and non-essential outings.